Marketing Dashboard Module for Supporting the Implementation of Digital Marketing in MSMEs - Fitriyana Dewi; Ekky Novriza Alam; Rachmadita Andreswari (Jurnal Rekayasa Sistem & Industri, 2021)
Mekarsari Village is a fostered village in Bandung district which has BUMDes. Mekarsari Village hasgreat potential, especially in the field of tea and coffee plantations. Several other MSMEs have productssuch as chips and other handicrafts. In general, MSMEs have difficulty increasing their competitiveness.The technology sector and competitors are the biggest challenges that must be overcome by MSMEs.Currently, the existence of a marketplace can help MSMEs to market and increase product sales.GambungStore is one of the marketplaces that is specifically intended as a marketing medium for MSMEproducts in Mekarsari Village. The existence of this marketplace can actually be optimized through a goodmarketing strategy. A good marketing strategy requires a periodic controlling process which can be doneby using information on the behavior of consumers towards the product. Information on consumerbehavior will be obtained in the marketing dashboard module in this research.